Momenty procesu skumulowanych świadczeń w indywidualnym ubezpieczeniu wieloopcyjnym - Homa, Magdalena (The Moments of Accumulated Payments in Individual Multi-State Insurance, 2006)
In the literature there are described the methods of analyzing and pricing in traditional life insurance, which permit to describe bases for insurer and estimate the "riskness" of individual contract. But in practice the traditional life insurance respects only the basic insurance products, which in reality are more complicated. This reason determined that in my article I consider a multistate insurance policies, which are more attractive and better adopted to the needs of clients. With the life insurance and in particular with the multi-state insurance is connected the analysis of the risk processes: loss or income of the insurer, total payments stream and accumulated payments. Therefore the essence of my work is the discussion and analysis of accumulated payments in multi-state insurance. I used the analysis of financial stream and their actuarial value proposed by Norberg. I presented the moments of accumulated payments in individual insurance. Knowledge of these moments permits to correct calculate premiums and reserves as well as to describe and estimate the "riskness" of individual contract. This is also the basis for further analysis of the insurance portfolio.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonometria (17); 2006; nr 1123, s. 202-216